Metachronous hepatic resection for liver only pancreatic metastases. (December 2020) - Schwarz, C.; Fitschek, F.; Primavesi, F.; Stättner, S.; Margonis, G.A.; Weiss, M.A.; Stavrou, G.A.; Oldhafer, K.J.; Kornprat, P.; Wundsam, H.; Fischer, I.; Längle, F.; et al.
Abstract: Background: The value of liver resection (LR) for metachronous pancreatic ductal adenocarcinoma (PDAC) metastases remains controversial. However, in light of increasing safety of liver resections, surgery might be a valuable option for metastasized PDAC in selected patients. Methods: We performed a retrospective, multicenter study including patients undergoing hepatectomy for metachronous PDAC liver metastases between 2004 and 2015 to analyze postoperative outcome and overall survival. All patients were operated with curative intent. Patients with oligometastatic metachronous liver metastasis with definitive chemotherapy (n = 8) served as controls. Results: Overall 25 patients in seven centers were included in this study. The median age at the time of LR was 63.8 years (56.9–69.9) and the median number of metastases in the liver was 1 (IQR 1–2). There were eight non-anatomical resections (32%), 15 anatomical minor (60%) and 2 major LR (8%). Postoperative complications occurred in eleven patients (eight Clavien-Dindo grade I complications (32%) and three grade IIIa complications (12%), respectively). The 30-day mortality was 0%. The median length of stay was 8.6 days (IQR 5–11). Median overall survival following LR was 36.8 months compared to 9.2 months in patients with metachronous liver metastasis with chemotherapy (p = 0007). Discussion: Liver resection for metachronous PDAC metastasis is safe and feasible in selected patients. To address general applicability and to find factors for patient selection, larger trials are urgently warranted. Highlights: Liver resection of metachronic PDAC metastases is safe. Careful patient selection is crucial to provide a satisfying outcome. Patients should receive neoadjuvant chemotherapy before LR.